2007
DOI: 10.1016/j.eplepsyres.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated p53 and lower MDM2 expression in hippocampus from patients with intractable temporal lobe epilepsy

Abstract: SummaryRecent studies of resected hippocampus from patients with intractable temporal lobe epilepsy (TLE) have yielded biochemical evidence of signalling pathways associated with apoptosis. The tumor suppressor and transcription factor p53 regulates expression of several genes involved in apoptosis. Cellular levels of p53 are regulated in part by murine double minute 2 (MDM2) via ubiquitination and degradation through the proteasome. Presently, we compared expression of p53 and MDM2 in resected hippocampus fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…This is consistent with immunohistochemical data that showed up‐regulation of p53 in the hippocampi of TLE patients (Xu et al ., ) along with a correlation between seizure‐activated neuronal death in rat hippocampi and p53 responses (Sakhi et al ., ; Araki et al ., ). However, neuropathological studies reveal that seizure‐mediated cellular death in TLE happens in a very limited manner (Bernasconi et al ., ; Mathern et al ., ; Liu et al ., ; Engel et al ., ). This might suggest a pro‐apoptotic effect of p53; this study suggested induced activities for several anti‐apoptotic and cytoprotective signalling cascades including AKT and RSK.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with immunohistochemical data that showed up‐regulation of p53 in the hippocampi of TLE patients (Xu et al ., ) along with a correlation between seizure‐activated neuronal death in rat hippocampi and p53 responses (Sakhi et al ., ; Araki et al ., ). However, neuropathological studies reveal that seizure‐mediated cellular death in TLE happens in a very limited manner (Bernasconi et al ., ; Mathern et al ., ; Liu et al ., ; Engel et al ., ). This might suggest a pro‐apoptotic effect of p53; this study suggested induced activities for several anti‐apoptotic and cytoprotective signalling cascades including AKT and RSK.…”
Section: Discussionmentioning
confidence: 99%
“…Years later and after several other reports on altered TP53 expression in seizure models, including the already mentioned study of Tan and colleagues [ 33 ], Xu et al found TP53 positive cells in the sclerotic hippocampus from TLE patients [ 31 ]. In the same year, Engel and colleagues detected significantly higher levels of TP53 by Western blotting in hippocampal tissues from TLE patients [ 50 ]. Our result on the elevated TP53 mRNA level extends and reinforces this data.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in human temporal epilepsy and animal temporal epilepsy models, the levels of normal p53 were elevated in the hippocampus, and the absence of p53 was related to worse seizure outcomes because of seizureinduced neuronal death. [37][38][39] Duan et al reported that epilepsy nerve cell apoptosis is regulated by the genes such as p53, Bcl, and Bax, and they exhibit a neuroprotective effect. 40) Therefore, p53 abnormalities might facilitate further intractability of seizures when epileptogenesis is established.…”
Section: The Role Of P53 In the Control Of Seizures In Patients With Lggmentioning
confidence: 99%